Prevalence of depressive symptoms amongst highly active antiretroviral therapy (HAART) patients in AIDSRelief Uganda - Constance Shumba; Ruth Atukunda; Richard Imakit; Peter Memiah (AOSIS, 2013)
There is limited data on the prevalence of depression in HIV and AIDS patients in Sub- Saharan Africa and little resources have been allocated to address this issue. Depression affects patient adherence to treatment and predisposes patients to resistance which poses a public health threat. It also affects quality of life and productivity of patients. From August 2008 to March 2009, 731 patient adherence surveys were administered to assess disease, treatment knowledge and services received. The primary variable of interest was patients' level of depressive symptoms score, constructed using factor analysis from five survey questions relating to: sadness, need to be alone, hopelessness and confusion and was categorized as no depressive symptoms (score 0), low depressive symptoms (score 1-2), moderate depressive symptoms (score 3-4) and high depressive symptoms (score 5-10). Majority of the patients on highly active antiretroviral therapy (HAART) (59%) were found to have depressive symptoms and this was more among women than men (66% vs 43%). There was some association of depressive symptoms with non-disclosure (70% of those who had not disclosed had depressive symptoms compared to 53% among those who had disclosed). There is a high prevalence of depressive symptoms among adult patients on HAART. There is need for in-depth evaluation to find out the root causes of depressive symptoms among HAART patients in AIDSRelief clinics. There is need to integrate mental health management in HIV care and treatment as well as training the existing health workers on mental health management.